TINJAUAN KETERAMPILAN TEKNIK DASAR SEPAKBOLA PADA TEAM SMPN 1 PANGEAN KAB. KUANTAN SINGINGI - Irsyadi, Yan Okta; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Based on the problems found, some students do not able to basic techniques of football, then the lack of knowledge of students to the basic techniques of football. Ability to escort and kicked the ball has not been so good. Based on this problem the researchers want to conduct research to determine the extent to which the basic techniques of football team SMPN 1 Pangean. This type of research is descriptive which aims to provide a systematic overview of the state of progress in the research object. The population in this study are all the players on the football team at SMPN 1 Pangean Kab. Kuantan Singingi by the number of players as many as 28 people. The sample in this study also numbered as many as 28 people (total sampling). Further data analysis techniques using deskriptif with analysis ability test basic techniques of football. Based on the results of data processing can be in the know that a Skill Level Basic Technique Football Team SMPN 1 Pangean Kab. Kuantan Singingi of the ability of the ball (heading) relatively less with the average value of 42.89 and the ability to hold a soccer ball (passing) classified as moderate by the Average category with an average of 47.54 and the ability of dribbling (dribbling) is quite good value an average of 64.54, and the ability to kick a ball (shooting) is quite an average of 54.60. Based on this basic engineering skills soccer Team SMPN 1 Pangean Kab. Kuantan Singingi quite enough with the average value of 53.Keywords : Observation, The Basic Techniques, Football